Social production in the creation of Malaysian 'literary' and authorship - Awang Pawi, Awang Azman; Nik Muhamad Affendi, Nik Rafidah; Hamdan, Rahimah (American Scientific Publishers, 2018)
A literary study is two-dimensional. The first dimension is the aspect of intrinsic literary study of the literature work itself. This is proven from the conventional and popular studies, for example, the studies of themes and issues in order to explore the message the author is trying to convey. Textual research can also be in the form of structural or narrative analysis. The studies done gave the impression that the external dimension has no role in creating literary texts. Therefore, the objective of this research is to prove that the external aspect or dimension of the text itself is important in producing literature. This study uses the authors from the state of Sabah as the subjects. This study summarises and proves that other external elements are also important in understanding the process of literary production in Malaysia.